Association between blood pressure classification defined by the 2017 ACC/AHA guidelines and coronary artery calcification progression in an asymptomatic adult population. Issue 1 (11th August 2021) - Won, Ki-Bum; Han, Donghee; Choi, Su-Yeon; Chun, Eun Ju; Park, Sung Hak; Han, Hae-Won; Sung, Jidong; Jung, Hae Ok; Chang, Hyuk-Jae
Abstract: Aims: Coronary artery calcium score (CACS) is widely used for cardiovascular risk stratification in asymptomatic population. We assessed the association of new blood pressure (BP) classification using the 2017 American College of Cardiology/American Heart Association guidelines with coronary artery calcification (CAC) progression according to age in asymptomatic adults. Methods and results: Overall, 10 839 asymptomatic Korean adults (23.4% aged ≤45 years) who underwent at least two CACS evaluations for health check-up were enrolled. Participants were categorized by age (≤45 and >45 years) and BP [normal (<120/<80 mmHg, untreated), elevated (120–129/<80 mmHg, untreated), Stage 1 hypertension (untreated BP 130–139/80–89 mmHg) or Stage 2 hypertension (BP ≥140/≥90 mmHg or anti-hypertensive use)] groups. CAC progression was defined as a difference of ≥2.5 between the square root (√) of the baseline and follow-up CACS. During a mean 3.3-year follow-up, the incidence of CAC progression was 13.5% and 36.3% in individuals aged ≤45 and >45 years, respectively. After adjustment for age, sex, diabetes, dyslipidaemia, obesity, current smoking, and baseline CACS, hazard ratios (95% confidence interval) for CAC progression in elevated BP, Stage 1 hypertension, and Stage 2 hypertension compared to normal BP were 1.43 (0.96–2.14) ( P = 0.077), 1.64 (1.20–2.23) ( P = 0.002), and 2.38 (1.82–3.12) ( P < 0.001) in the ≤45 years group and 1.11 (0.95–1.30) ( P = 0.179), 1.17 (1.04–1.32) ( P = 0.009), and 1.52 (1.39–1.66) ( P < 0.001) in the >45 years group, respectively. Conclusion: Newly defined Stage 1 hypertension is independently associated with CAC progression in asymptomatic adults regardless of age. Graphical abstract: